MODERASI KEPEMILIKAN INSTITUSIONAL : DAPATKAH MEMPENGARUHI FAKTOR KEUANGAN TERHADAP STRUKTUR MODAL - Dirvi Abbas; Sigit Budi Santoso; Daniel Rahandri (Jurnal Riset Akuntansi Politala, 2023)
Abstract The aim of this research was to examine how profitability, liquidity, tangibility, and non-debt tax shield impact the capital structure of manufacturing companies listed on the IDX during the period of 2017-2021, with institutional ownership as a moderating factor. The sample was selected using purposive sampling based on predetermined criteria, and panel data regression analysis was used for data analysis. The hypothesis testing was conducted with a significance level of 5%. The findings revealed that only the variable of non-debt tax shield had a negative effect on the capital structure, while the variables of profitability, liquidity, and tangibility had no impact. The institutional ownership was found to enhance the influence of non-debt tax shields on capital structure, but it did not moderate the effect of profitability, liquidity, and tangibility on the capital structure.